ПЕРСПЕКТИВНІ МОДЕЛІ ТОРГІВЛІ, ЗАСНОВАНІ НА ПРИНЦИПАХ ЦИРКУЛЯРНОЇ ЕКОНОМІКИ: ТОВАРОЗНАВЧИЙ АСПЕКТ - ДРАЖНИЦЯ, Сергій; КАЛІНСЬКИЙ, Євген; ЛИХОГОД, Олександр (Development Service Industry Management, 2026)
У даній статті автори розкривають суть циркулярної економіки та її принципів (повторне використання, вторинна переробка, тощо), визначають рівень впливу принципів циркулярної економіки на якість та асортимент товарів, визначаючи перспективні організаційні моделі торговельного обслуговування споживачів.Також у статті авторами здійснено короткий аналіз функціональних моделей організації торгівлі в Україні та за кордоном із визначенням їх впливу на асортимент та якість товарів, а також екологічний стан навколишнього середовища.На основі проведеного аналізу авторами запропоновано декілька перспективних моделей організації торгівлі, які ґрунтуються на принципах циркулярної економіки та сприяють розширенню асортименту товарів і послуг в торгівлі, сприяють підвищенню їх якості та мінімізують негативний вплив такої господарської діяльності на екологію оточуючого середовища.In this article, the authors reveal the essence of the circular economy and its principles (reduction of consumption, reuse, recycling), determine the level of influence of the principles of the circular economy on the quality and assortment of goods, and identify promising organizational models of retail customer service. It has been established that adherence to the principles of the circular economy in the process of organizing consumer trade services not only helps reduce the negative impact of economic activity in this industry on the environmental situation, but also ensures an expansion of the range of goods and an improvement in their quality.The authors also conducted a brief analysis of functional models of trade organization in Ukraine and abroad, determining their impact on the assortment and quality of goods, as well as the ecological state of the environment. As a result of the analysis, it was found that most modern and progressive models of organizing trade services (both in Ukraine and abroad) are based on automation and informatization processes, the use of artificial intelligence resources (AI agents), virtual (VR) and augmented (AR) reality, as well as the resources of the buyers themselves (self-service), without paying due attention to the environment.Based on the analysis conducted, the authors proposed several promising models of trade organization that are based on the principles of the circular economy and contribute to expanding the range of goods and services in trade, improving their quality, and minimizing the negative impact of such economic activity on the environment. According to the authors, such promising green trade models, which, in addition to improving the ecology of the environment, will also contribute to expanding the range of goods and services, their quality and level of service, are rental and leasing models, organization of the secondary market and exchange platforms, restoration of packaging turnover, buyback, and integrated models.